A Self‐Powered Brain‐Linked Vision Electronic‐Skin Based on Triboelectric‐Photodetecing Pixel‐Addressable Matrix for Visual‐Image Recognition and Behavior Intervention. (3rd April 2018) - Dai, Yitong; Fu, Yongming; Zeng, Hui; Xing, Lili; Zhang, Yan; Zhan, Yang; Xue, Xinyu
Abstract: A new self‐powered brain‐linked vision electronic‐skin (e‐skin) for mimicking retina is realized from Polypyrrole/Polydimethysiloxane (Ppy/PDMS) triboelectric‐photodetecting pixel‐addressable matrix. The e‐skin can be driven by human motion, so no external electricity power is needed in both photodetecting and signal transmitting processes. The triboelectric output is significantly dependent on the photo illumination, which can act as visual bionic electric impulse. Taking blue illumination (405 nm) as an example, as the e‐skin is exposed to 100 µW cm −2 illumination, the output current decreases from 7.5 to 4.9 nA, and the photosensitivity is 34.7. And the photosensitivity of the e‐skin keeps stable with different bending angles and force. The e‐skin is flexible enough to combine with human body and can be driven by blinking eyes to detect UV illumination. In addition, the 4 × 4 photodetecting unit matrix in the e‐skin can map single‐point and multipoint illumination‐stimuli (visual‐image recognition) via the multichannel data acquisition method. Furthermore, the e‐skin can directly transmit photodetecting signals into mouse brain for participating in the perception and behavior intervention. This new self‐powered perception device can lower down the production cost of traditional complex sensory‐substitution system, and can be easily extended to various brain–machine interaction applications. Abstract : A self‐powered brain‐linked vision electronic‐skin for mimicking retina is realized from triboelectric‐photodetecting pixel‐addressable matrix. The device can combine the electricity‐power generating, photodetecting, and neurobionics of signal transmission into one single chemical/physical process. This new device can lower down the production cost of traditional complex sensory substitution system and provoke a new research direction for brain–machine interactions.